Empowering Vulnerable Groups through Legal Protection and Guidance: A Case Study of PCA Jetis Ponorogo - Shafa, Ulya; Febriansyah, Ferry Irawan; Agiyanto, Ucuk; Nurhana, Lina (Borobudur Journal on Legal Services, 2026)
Vulnerable groups such as women, the elderly, single mothers, and people with disabilities still face various legal issues, including inheritance disputes, debt-receivables agreements, and domestic violence (KDRT). To answer these problems, PCA ‘Aisyiyah Jetis acts as a companion partner who functions as a community paralegal. Low legal literacy, limited access to professional legal aid, and case resolution that is limited to internal mediation are the main obstacles. This service activity aims to strengthen legal protection for vulnerable groups through increasing legal literacy and case assistance. The strategies used include legal counselling, the establishment of Community Legal Service Posts, local paralegal regeneration, and the use of digital technology in the form of Community Legal Service Information Systems and Archives (SILAH-Community). The implementation method uses a participatory approach with partners through socialization, training, and direct mentoring. Provisional results show an increase in members’ understanding of legal rights, the formation of community paralegal cadres, and the use of digital systems for case documentation. Through community-based legal assistance, it can be a model of legal protection that is adaptive, cheap, and sustainable for vulnerable groups.